Root density of Megathyrsus maximus BRS Quênia and Urochloa brizantha BRS Piatã in silvipastorl systems - Silva, Hérica André da; Prudente Velozo, Amanda; Xavier de Freitas, Paulo Vitor Divino; Pacheco, Abílio Rodrigues; Neves Calil, Francine; Silva-Neto, Carlos de Melo e (Revista Ecologia e Nutrição Florestal - ENFLO, 2024)
The objective of this study is to determine the root density of Megathyrsus maximus and Urochloa brizantha forages at a depth of 20 cm alone, in relation to their distances from the tree component in two systems of livestock-forest integration with two entities. For this study, the following livestock-forest integration systems were carried out: a system with 3 years of composting by AEC-043 eucalypts clones spaced in strips of simple lines of 15x2 m and the forage component Megathyrsus maximus cv. Quenia; The other system requires 2 years of growth and AEC-2034 eucalyptus clones with the same forest root and forage component Urochloa brizantha BRS Piatã. Five transects were collected randomly in each of two livestock-forest integration systems and measured 5 distances from the tree component for root collection in the dry period. The roots are separated and dried only for density evaluation. In the area as a livestock-forest integration system with 2 years of life with eucalypts clones AEC-2043 and Urochloa brizantha forage, a higher average production of total density of roots at a distance of 5 meters from the tree component, with value of 11.75 g and less root density at zero distance with 8.63 g. In the 3-year livestock-forest integration system, with AEC-043 eucalyptus clones and Megathyrsus maximus forage component, the highest concentration of root density occurred at distance zero with 10.23 g and lowest root density at distance 5 m with 4.45 g. In both systems, eucalyptus influenced the root system of the forage grass.